Minor dietary components intrinsic to goat milk and goat milk formulas. (June 2021) - Tolenaars, Louise; Romanazzi, Donato; Carpenter, Elizabeth; Gallier, Sophie; Prosser, Colin G.
Abstract: Limited information exists on minor dietary components in paediatric formulas made from goat milk. This study confirmed concentrations of nucleotides, polyamines and sialic acid in whole goat milk (WGM; 4.22 mg nucleotides, 66.4 μg polyamines and 19.4 mg sialic acid per 100 mL) and their retention in infant and young child formulas containing WGM. Added lactose further contributes up to 20% of the total sialic acid content in infant formula. This study demonstrates that WGM is a natural source of minor components for paediatric formulas, limiting the need for addition of specific ingredients.